Victorian fairy tales the revolt of the fairies and elves - Zipes, Jack David (New York Routledge, 1987)
A collection of fairy tales by Victorian writers, including Lewis Carroll, Charles Dickens, Oscar Wilde, and Rudyard Kipling, with illustrations from the same period.
Bibliography: p. [373]-381.
Keywords: Fairy tales -- Great Britain; English fiction -- 19th century; Fairy tales; Short stories